a INOVASI MEDIA PEMBELAJARAN BERBASIS ICT UNTUK PENDIDIKAN AGAMA ISLAM DI SEKOLAH UMUM: INOVASI MEDIA PEMBELAJARAN BERBASIS ICT UNTUK PENDIDIKAN AGAMA ISLAM DI SEKOLAH UMUM - subhan, ah. subahn; Wahidin (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2025)
This study aims to explore innovative learning media based on Information and Communication Technology (ICT) applicable to Islamic Religious Education (PAI) in public schools and to evaluate their impact on the quality of teaching and learning processes. The research employed a descriptive qualitative method with data collected through observations, interviews, and document analysis. The findings indicated that ICT-based media, such as interactive videos, Islamic educational applications, and e-learning platforms, enhance students’ understanding of PAI materials and encourage active engagement in learning. Challenges included limited technological infrastructure in schools and insufficient teacher training in ICT utilization. To address these issues, teacher training, improved technological facilities, and support from various stakeholders, including the government, are recommended. This study concludes that ICT-based learning media innovations have significant potential to improve the effectiveness of PAI instruction, provided they are supported by adequate preparation and resources.